2022
DOI: 10.3389/fnagi.2022.980998
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic efficacy of transcranial magnetic stimulation in managing Alzheimer’s disease: A systemic review and meta-analysis

Abstract: BackgroundRepetitive Transcranial Magnetic Stimulation (rTMS) is widely used to treat Alzheimer’s Disease. However, the effect of rTMS is still controversial. The purpose of the present study is to evaluate the effectiveness of rTMS on cognitive performance of AD patients.MethodsWe systematically searched relevant literatures in four major databases - PubMed, EMBASE, Web of Science, and the Cochrane Central Register of Controlled Trials [Central] before 28th April 2022. Both randomized controlled trials and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Consistent with previous studies, Xie et al [ 85 ] examined the effects of rTMS on memory and executive function and found no substantial disparities compared with the control group. Similarly, Wei et al [ 23 ] discovered that while rTMS did not effectively ameliorate patients’ memory, executive function, or emotions, it was capable of enhancing their daily life abilities. Iimori et al [ 86 ] emphasized that, when compared to patients with depression, there was no evidence supporting the effectiveness of rTMS in improving the executive function of patients with AD and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with previous studies, Xie et al [ 85 ] examined the effects of rTMS on memory and executive function and found no substantial disparities compared with the control group. Similarly, Wei et al [ 23 ] discovered that while rTMS did not effectively ameliorate patients’ memory, executive function, or emotions, it was capable of enhancing their daily life abilities. Iimori et al [ 86 ] emphasized that, when compared to patients with depression, there was no evidence supporting the effectiveness of rTMS in improving the executive function of patients with AD and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased motor excitability and cortical reorganization in AD may explain the frontomedial shift in motor areas, which is interpreted as a compensatory mechanism that preserves motor programming despite AD progression [21]. Most studies have shown that rTMS can effectively enhance the cognition [22,23], emotion [24], and language [25][26][27] in patients with AD. However, other studies have provided different perspectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in 2008, the United States Food and Drug Administration approved the use of TMS in drug-resistant depression treatment ( 34 ). Currently, TMS is used in the treatment of nervous system diseases such as SCI ( 35 ), Alzheimer’s disease ( 36 ), Parkinson’s disease ( 37 ), multiple sclerosis ( 38 ), stroke-related disability ( 39 ), and schizophrenia ( 40 ). TMS use has achieved gratifying results in basic research and clinical trials; hence, it is a potential treatment method for nervous system diseases.…”
Section: Basic Principles and Classification Of Tmsmentioning
confidence: 99%
“…These pulses serve to stimulate neurons in the brain which, in turn, results in changes in cortical excitability [1]. Repeated stimulation of this nature has been correlated with improvements in cognitive functioning and depression symptoms, and thus has been implemented as a form of treatment for varieties of neurological and psychiatric disorders [2]- [4].…”
Section: Introductionmentioning
confidence: 99%